UNVEILING PITUITARY PARADOX: OCTREOTIDE LONG-ACTING RELEASE (LAR) INDUCED APOPLEXY IN POSTOPERATIVE RESIDUAL MACROADENOMA - Hong, Lee Hoong; Goh, Kian Guan; Amin, Mohd Syazwan (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND The development of a somatostatin analogue (SSA) has revolutionized the treatment of acromegaly. Octreotide LAR is a long-acting release formulation of SSA, often used as an alternative when surgery is not possible in patients with acromegaly or as an adjuvant therapy in post-operative patients with residual pituitary adenoma. Pituitary apoplexy, characterized by infarction or bleeding of the pituitary gland, is a rare condition. CASE An 18-year-old male with a clinical and biochemical diagnosis of acromegaly underwent transsphenoidal surgery in November 2021 with incomplete tumour resection, complicated by pituitary apoplexy after administration of octreotide LAR. Post-operatively, he had residual pituitary adenoma with optic chiasm compression and persistent elevations of insulin-like growth factor 1 (IGF-1) (1.7x > upper limit of normal) and growth hormone (GH) level (10x > normal limit). After extensive discussion, the patient was started on medical treatment, cabergoline 0.5 mg twice weekly, but failed to achieve biochemical control despite continued use for 9 months. Subsequently, octreotide LAR 30 mg monthly was started, aiming to achieve better biochemical control and shrink the tumour size while awaiting stereotactic radiosurgery. Unfortunately, 6 weeks after the first injection of octreotide LAR, he developed a sudden severe headache and visual disturbance, presenting clinically with bitemporal hemianopia, subsequently diagnosed with pituitary apoplexy on cranial MRI. Octreotide LAR was discontinued. Patient underwent repeated transsphenoidal surgery, which was uncomplicated, albeit with pre-existing central hypothyroidism and hypocortisolism. CONCLUSION Pituitary apoplexy is one of the rare complications of SSA. However, clinicians need to maintain a high level of suspicion for this complication if the patient presents with sudden headache with or without neuro-ophthalmic signs after receiving SSA, given its significant morbidity and potential fatality.